Preparation method and application of photoresponse type modified polyvinyl chloride nanofiber
Photoresponsive modified polyvinyl chloride nanofibers are prepared through electrospinning and ionic liquid technology, which solves the problems of low efficiency and environmental pollution in traditional gold recycling technology, and realizes efficient selective adsorption of Au3+ and effective recovery of gold resources.
Patent Information
- Application Number
- CN202411370172.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Traditional gold recycling technology has problems with low adsorbent efficiency and poor selectivity, and PVC waste treatment methods lead to environmental pollution and lack efficient gold resource recycling technology.
Electrospinning technology is used to prepare polyvinyl chloride nanofibers, and the surface is positively charged functionalized through ionic liquid modification technology. Combined with the photoresponse mechanism, the adsorption effect on Au3+ is improved, and a high adsorption capacity and selectivity is prepared. Modified nanofibers.
It realizes efficient selective adsorption of Au3+ with the assistance of visible light, improves the recovery rate and capacity of gold, is suitable for gold resource recycling in complex industrial wastewater, and provides a new environmentally friendly resource reuse method.
Smart Images

Figure CN119243354A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method and application of light-responsive modified polyvinyl chloride nanofibers. Background Art
[0002] Gold is one of the most common precious metals in life. Currently, its consumption has increased dramatically not only as jewelry, but also because of its good physical and chemical properties, it is used in electronic products, chemical catalysis, aerospace and other fields. However, the reserves of natural high-grade gold resources are limited, and the mining cost is increasing with the consumption of resources. There are abundant secondary gold resources in existing electronic waste and some industrial wastewater, and their recycling and reuse can greatly make up for the consumption of natural gold resources. Therefore, the secondary recovery and utilization of gold resources is extremely important for the sustainable development strategy.
[0003] Polyvinyl chloride (PVC) is a common high molecular polymer. Frequent use will result in a large amount of PVC-containing waste. The treatment of PVC waste is usually carried out by landfill and incineration, but such treatment methods will cause new environmental pollution problems. However, since PVC contains abundant chlorine group side chains, it can be used as a reaction site for modifying PVC. Therefore, using PVC as a matrix material for modification can transform environmentally harmful PVC into a beneficial new material, which is of great significance to the environment and resource recycling.
[0004] Traditional gold recovery technology has the problems of low adsorbent efficiency and poor selectivity. Electrospinning technology can be used to prepare nanofibers with a high specific surface area. The fiber surface is functionalized with positive charges by combining ionic liquid modification technology, while providing more nitrogen active sites. In addition, since the grafted pyridine ring has a planar conjugated structure and exhibits a good response to light, the adsorption effect of gold in the solution can be significantly improved under the irradiation of visible light. Therefore, this type of light-responsive adsorbent material can be used as a potential material for adsorbing and recovering gold from wastewater. Summary of the invention
[0005] The present invention adopts a simple method to prepare a light-responsive modified polyvinyl chloride nanofiber, and uses it to 3+ The present invention uses polyvinyl chloride (PVC) as the matrix material, prepares PVC nanofibers by electrospinning technology, and further modifies the PVC nanofibers by ionic liquid modification, successfully preparing a modified PVC nanofiber with excellent adsorption performance. The nanofiber has excellent adsorption performance on Au 3+The maximum adsorption capacity of the adsorbent can reach 1243.75 mg / g under the condition of visible light assisted promotion. The adsorption process conforms to the pseudo-second-order kinetic model and the Langmuir isotherm adsorption model, and it shows good adsorption performance for Au in the complex strongly acidic industrial wastewater environment. 3+ The high selectivity of Au 3+ It has a high selective adsorption capacity. The modified nanofiber adsorption material prepared by combining electrospinning technology and ionic liquid technology shows good responsiveness to light. The modified nanofiber prepared by the present invention can significantly improve the adsorption rate and adsorption capacity by providing visible light irradiation, providing a new technical method for the recovery of gold in wastewater.
[0006] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is to use polyvinyl chloride (PVC) as the matrix material, adopt electrospinning technology to prepare nanofibers, and use 4,4-bipyridine as the modified functional group to prepare ionic liquid-modified PVC nanofibers.
[0007] The preparation method of the modified PVC nanofibers is as follows:
[0008] (1) Preparation of PVC electrospinning nanofibers:
[0009] 1.2-1.6g of polyvinyl chloride (PVC) and 8.4-8.8g of a mixed solution of DMF and THF (w / w=1:1) were added to a beaker, and stirred at room temperature for 6 hours to obtain a uniform and transparent spinning solution (wt=12%-16%). The obtained spinning solution was then placed in a 10mL syringe and spun in an electrospinning machine; the optimized parameters of the spinning machine were set as follows: voltage of 15.0KV, spinning solution flow rate of 1.0mL / h, drum speed of 400r / min, receiving distance of 15cm, spinning temperature and humidity of 25±1℃ and 60±5%, respectively.
[0010] (2) Preparation of modified PVC nanofibers: The prepared PVC nanofibers were cut into small pieces of 1*1 cm, and then 0.2 g of the small pieces of PVC nanofibers were weighed and placed in a three-necked flask with 0.14-0.42 g of 4,4-bipyridine and 0.5-1.5 g of potassium hydroxide, and then 40 mL of acetonitrile was added as a solvent. The mixture was reacted at 80°C with magnetic stirring for 1-3 days. After the reaction, the fiber powder was washed with pure water for more than 3 times and then centrifuged. It was then vacuum dried at 80°C for 8 hours to obtain modified PVC nanofibers.
[0011] As a preferred spinning solution, the weight content is 12%, the amounts of 4,4-bipyridine and potassium hydroxide are 0.28 g and 1.0 g respectively, and the reaction time is 3 days.
[0012] Another object of the present invention is to use the light-responsive modified polyvinyl chloride nanofibers prepared by the present invention as an adsorption material for Au 3+ Selective recovery of gold from wastewater.
[0013] The modified PVC nanofibers prepared by the present invention have abundant nitrogen-containing groups, which can serve as adsorption sites for Au. 3+ There is a strong interaction between them, which 3+ In addition, since the modified PVC nanofibers have good light response properties, the electron transfer between them and the gold in the solution can be promoted under light conditions, 3+ Reduced to Au(0), thus promoting the entire adsorption process.
[0014] Compared with the prior art, the advantages and positive effects of the present invention are:
[0015] 1. The modified polyvinyl chloride nanofibers of the present invention are modified by ionic liquid to make the surface of the prepared nanofibers rich in positive charge, so as to achieve the effect of reacting with AuCl4 in aqueous solution which is negatively charged. - Carry out selective enrichment adsorption.
[0016] 2. The modified polyvinyl chloride nanofiber of the present invention is 3+ The adsorption process involves multiple reaction mechanisms such as electrostatic effect, coordination effect and redox reaction, so it has a higher adsorption capacity and better adsorption effect.
[0017] 3. The modified polyvinyl chloride nanofibers of the present invention show good responsiveness to light, and can further enhance the responsiveness to Au under the promotion of visible light. 3+ The adsorption effect can effectively solve the problem of gold adsorption, recovery and removal in high concentration solutions, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0019] Figure 1 The figure is a preparation process diagram of the modified polyvinyl chloride nanofiber of the present invention;
[0020] Figure 2 is a scanning electron microscope image of the modified polyvinyl chloride nanofiber of the present invention;
[0021] Figure 3 This is the analysis diagram of the effect of pH on the adsorption process;
[0022] Figure 4 Au under light and no light conditions 3+ Analysis of the effect of initial concentration on the adsorption process;
[0023] Figure 5 This is an analysis diagram of the effect of time on the adsorption process under conditions of illumination and no illumination;
[0024] Figure 6 To modify polyvinyl chloride nanofibers to Au in a complex mixed solution 3+ Selective impact analysis diagram;
[0025] Figure 7 This is the analysis diagram of the effect of temperature on the adsorption process;
[0026] Figure 8 This is the photoresponse diagram of modified polyvinyl chloride nanofibers. DETAILED DESCRIPTION
[0027] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0029] Embodiment 1:
[0030] In order to achieve the above purpose, the technical solution adopted by the present invention is to use polyvinyl chloride (PVC) as the matrix material, adopt electrostatic spinning technology to prepare nanofibers, and use 4,4-bipyridine as the modified functional group to prepare ionic liquid modified PVC nanofibers. 3+ The Au is bonded through electrostatic interaction, coordination and redox interactions. 3+ In addition, light is used to promote the adsorption process to achieve the selective adsorption of Au in water. 3+ Efficient recycling.
[0031] The preparation process of the modified polyvinyl chloride nanofiber in this embodiment is as follows:
[0032] (1) Preparation of PVC electrospinning nanofibers: 1.2 g of polyvinyl chloride (PVC) and 8.8 g of a mixed solution of DMF and THF (w / w = 1:1) were added to a beaker, and stirred at room temperature for 6 h to obtain a uniform and transparent spinning solution (wt = 12%), and then the obtained spinning solution was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 1.0 mL / h, drum speed of 400 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24 ° C and 55%, respectively.
[0033] (2) Preparation of modified PVC nanofibers: The prepared PVC nanofibers were cut into small pieces of 1*1 cm, 0.2 g of the small pieces of PVC nanofibers were weighed, and placed in a three-necked flask with 0.14 g of 4,4-bipyridine and 0.5 g of potassium hydroxide, and 40 mL of acetonitrile was added as a solvent. The mixture was then reacted at 80°C with magnetic stirring for 3 days. After the reaction, the fiber powder was washed with pure water 3 times and then centrifuged. It was then vacuum dried at 80°C for 8 hours to obtain light-responsive modified polyvinyl chloride nanofibers.
[0034] Embodiment 2:
[0035] In order to achieve the above purpose, the technical solution adopted by the present invention is to use polyvinyl chloride (PVC) as the matrix material, adopt electrostatic spinning technology to prepare nanofibers, and use 4,4-bipyridine as the modified functional group to prepare ionic liquid modified PVC nanofibers. 3+ The Au is bonded through electrostatic interaction, coordination and redox interactions. 3+ In addition, light is used to promote the adsorption process to achieve the selective adsorption of Au in water. 3+ Efficient recycling.
[0036] The preparation process of the light-responsive modified polyvinyl chloride nanofiber of this embodiment is as follows: Figure 1 As shown, the preparation method is as follows:
[0037] (1) Preparation of PVC electrospinning nanofibers: 1.4 g of polyvinyl chloride (PVC) and 8.6 g of a mixed solution of DMF and THF (w / w = 1:1) were added to a beaker, and stirred at room temperature for 6 h to obtain a uniform and transparent spinning solution (wt = 14%), and then the obtained spinning solution was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 1.0 mL / h, drum speed of 400 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ° C and 60%, respectively.
[0038] (2) Preparation of modified PVC nanofibers: The prepared PVC nanofibers were cut into small pieces of 1*1 cm, 0.2 g of the small pieces of PVC nanofibers were weighed, and they were mixed with 0.28 g of 4,4-bipyridine and 1.0 g of potassium hydroxide in a three-necked flask, and then 40 mL of acetonitrile was added as a solvent. The mixture was reacted at 80°C with magnetic stirring for 3 days. After the reaction, the fiber powder was washed with pure water for 3 times and then centrifuged. It was then vacuum dried at 80°C for 8 hours to obtain light-responsive modified polyvinyl chloride nanofibers.
[0039] The light-responsive modified polyvinyl chloride nanofibers prepared in this example are used as adsorption materials in the recovery of gold in wastewater.
[0040] Sample characterization of this example:
[0041] like Figure 2 As shown, the surface morphology of the original PVC nanofibers (wt = 12% -16%) and the modified PVC nanofibers (wt = 14%) were observed using a scanning electron microscope. It can be clearly observed that the diameter of the original PVC nanofibers (wt = 14%) is uniform and has no beading phenomenon, showing a mesh structure, and the diameter is mainly distributed around 800nm. In addition, the nanofibers with wt of 12% and 16% have poor morphology and uneven thickness. Due to the action of external force, the modified PVC fibers become shorter than the original PVC fibers after being crushed. At the same time, its diameter becomes thicker than the original fibers and it can be clearly observed that the surface of the modified fibers becomes rough. The reason for this change may be that several fibers of the original PVC fibers are entangled together during the modification process. On the other hand, the holes on the surface of the modified PVC fibers may be caused by the dissolution of the generated potassium salt during the washing process. In short, the changes in the morphology of the modified fibers show the successful grafting of ionic liquids on the surface of the nanofibers.
[0042] Considering the influence of different factors on the adsorption results, static adsorption was used to study the adsorption of Au by modified PVC nanofibers under different conditions. 3+ The adsorption capacity of Au(Ⅲ) was studied. The influencing factors mainly include solution pH (1-9), initial concentration of Au(Ⅲ) solution (200-1400 mg / L), adsorption temperature (25-45℃) and contact time (1-7200 min). The whole adsorption process was carried out in a constant temperature oscillator. 3+ The concentration was determined by ICP-OES. The theoretical adsorption capacity is calculated according to the following formula: The adsorption amount (mg / g) of the adsorbent is calculated according to the following formula (1):
[0043]
[0044] Where: Q e (mg / g) is the adsorption capacity; C0 (mg / L) is the initial concentration of the solution; C e (mg / L) is the equilibrium concentration of the solution; V (mL) is the volume of the solution; W (g) is the mass of the adsorbent.
[0045] like Figure 3 As shown in Figure 2, the modified PVC nanofibers showed good kinetics for Au in a wide pH range (1-3). 3+ It has a good adsorption effect, and has the best adsorption capacity at pH = 2. At pH = 4, the adsorption capacity drops sharply, and after the pH is greater than 4, the adsorption capacity begins to gradually decrease. The reason for this phenomenon can be explained by the Zeta potential in the figure. It is mainly because when the pH is less than 3.73, the surface of the modified PVC nanofiber of the adsorption material has a positive charge, which is easy to react with the AuCl4 with a negative charge on the surface. - The adsorption behavior occurs between them through electrostatic attraction.
[0046] In order to study the effect of initial concentration on the adsorption capacity of modified PVC nanofibers, Au with a concentration of 200-1400 mg / L was prepared. 3+ The experiment was carried out at 25°C and the pH value of the solution was 2. Figure 4 It can be seen that there is a positive correlation between the adsorption capacity and the initial concentration under the conditions of light and without light. 3+ When the initial concentration reached 800 mg / L, the adsorption was basically saturated. Interestingly, under light conditions, the adsorption capacity increased by nearly one-fold compared to that without light. These results indicate that light promotes the occurrence of adsorption behavior.
[0047] The effect of contact time on the adsorption process is as follows Figure 5 As shown in the figure, within the initial contact time of 1080 minutes, the adsorption capacity increases relatively rapidly, reaching about 2 / 3 of the maximum adsorption capacity. This may be because the modified PVC nanofibers have a large number of adsorption sites at this time. After this time point, the adsorption rate climbs relatively slowly, and the adsorption basically reaches equilibrium at 3600 minutes. This result may be related to the fact that the adsorption sites of the modified PVC nanofibers are largely occupied. In addition, a large amount of Au 3+ Adsorption leads to a decrease in the ion concentration in the solution, thereby weakening the driving force for mass transfer. More interestingly, the experiment found that the adsorption capacity under light conditions increased significantly compared to the adsorption capacity without light in the same period of time. In other words, adsorption under light can reach the adsorption capacity without light in a shorter time, greatly improving the adsorption efficiency.
[0048] The selective experiment was to add 10 mg of modified PVC nanofibers into 25 mL of 200 mg / L Fe 3+ ,Co 2+ , Ni 2+ , Cd 2+ , Pb 2+ and Au 3+ The results are shown in Figure 6 As shown in the figure, the modified PVC nanofibers have a great influence on the Au 3+ It showed high adsorption capacity, but had little adsorption to other ions. 3+ The modified PVC nanofibers have excellent selectivity for Au 3+ The selectivity of the ion is attributed to its surface rich in positive charges, which easily react with AuCl4 in the form of negative ions. - Static electricity is generated between them.
[0049] In addition, it should be noted that, at present, due to limited experimental conditions, the selective adsorption effect of the light-responsive modified polyvinyl chloride nanofibers provided by the present invention is not limited to Fe 3+ ,Co 2+ , Ni 2+ , Cd 2+ , Pb 2+ and Au 3+ Au in the mixed solution 3+ Specific recognition.
[0050] The effect of temperature on the adsorption process was investigated by thermodynamic experiments at different temperatures of 25°C-45°C (contact time 1080 min, pH = 2). The results are as follows: Figure 7 As shown. It can be concluded that within a certain temperature range, as the temperature gradually rises, the adsorption of Au by the adsorbent material 3+ The adsorption capacity of Au is also expanding, indicating that high temperature conditions are conducive to the adsorption of Au. 3+ This result may be due to the fact that Au 3+ The rate of diffusion is accelerated.
[0051] In order to investigate the mechanism of light promoting the adsorption of modified PVC nanofibers, the photocurrent response curve was determined by electrochemical experiments. Figure 8 As shown in the figure, under the irradiation of xenon light source, the photocurrent response curve of modified PVC nanofibers was plotted by controlling the conditions of alternating illumination and no illumination for 50 seconds each. It can be seen from the figure that under the condition of illumination, the current density of modified PVC nanofibers increased, indicating that illumination promoted the transfer of charge, which was beneficial to the reduction of Au(Ⅲ) during the adsorption process, and further promoted the adsorption process.
[0052] Embodiment 3:
[0053] The photoresponsive modified polyvinyl chloride nanofiber of this embodiment is prepared as follows:
[0054] (1) Preparation of PVC electrospinning nanofibers: 1.6 g of polyvinyl chloride (PVC) and 8.4 g of a mixed solution of DMF and THF (w / w = 1:1) were added to a beaker and stirred at room temperature for 6 h to obtain a uniform and transparent spinning solution (wt = 16%). The obtained spinning solution was then placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 1.0 mL / h, drum speed of 400 r / min, receiving distance of 15 cm, spinning temperature and humidity of 26 ° C and 65%, respectively.
[0055] (2) Preparation of modified PVC nanofibers: The prepared PVC nanofibers were cut into small pieces of 1*1 cm, 0.2 g of the small pieces of PVC nanofibers were weighed, and placed in a three-necked flask with 0.42 g of 4,4-bipyridine and 0.8 g of potassium hydroxide, and 40 mL of acetonitrile was added as a solvent. The mixture was reacted at 80°C with magnetic stirring for 2 days. After the reaction, the fiber powder was washed with pure water three times and then centrifuged. It was then vacuum dried at 80°C for 8 hours to obtain light-responsive modified polyvinyl chloride nanofibers.
[0056] The light-responsive modified polyvinyl chloride nanofiber provided by the present invention is used as an adsorption material in the recovery of gold in waste water.
[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing light-responsive modified polyvinyl chloride nanofibers, characterized in that: Using polyvinyl chloride (PVC) as the matrix material, the nanofibers were prepared by electrospinning technology, and 4,4-bipyridine was used as the modified functional group to prepare ionic liquid-modified PVC nanofibers. The specific preparation steps are as follows: (1) Preparation of PVC electrospinning nanofibers: Add 1.2-1.6 g of polyvinyl chloride and 8.4-8.8 g of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (DHF) into a beaker, stir at room temperature for 6 hours to obtain a uniform and transparent spinning solution, then place the obtained spinning solution into a 10 mL syringe and spin it in an electrospinning machine to obtain PVC nanofibers; (2) Preparation of modified PVC nanofibers: The PVC nanofibers prepared in step (1) were cut into small pieces of 1*1 cm, and then 0.2 g of the small pieces of PVC nanofibers were weighed and placed in a three-necked flask with 0.14-0.42 g of 4,4-bipyridine and 0.5-1 g of potassium hydroxide, and then 40 mL of acetonitrile was added as a solvent. The mixture was reacted at 80°C with magnetic stirring for 1 to 3 days. After the reaction, the fiber powder was washed with pure water for more than 3 times and then centrifuged. It was then vacuum dried at 80°C for 8 hours to obtain modified PVC nanofibers.
2. The method for preparing the light-responsive modified polyvinyl chloride nanofiber according to claim 1, characterized in that: In step (1), the parameters of the electrospinning machine are set as follows: voltage is 15.0 KV, spinning solution flow rate is 1.0 mL / h, drum speed is 400 r / min, receiving distance is 15 cm, spinning temperature and humidity are 25±1°C and 60±5%, respectively.
3. The method for preparing the light-responsive modified polyvinyl chloride nanofiber according to claim 1, characterized in that: In step (1), the mass percentage of DMF and DHF in the mixed solution is 1:1, and the mass percentage of the obtained transparent spinning solution is 12%-16%.
4. The light-responsive modified polyvinyl chloride nanofibers prepared by the method for preparing the light-responsive modified polyvinyl chloride nanofibers according to claims 1 to 3 are used as adsorption materials for Au 3+ Selective recovery.
Citation Information
Patent Citations
Surface modification method for polyvinylidene fluoride (PVDF) film or polyvinyl chloride (PVC) film
CN102558595A
Method for modifying hollow fiber membrane through electro-chemistry surface-initiated atom transfer radical polymerization
CN105056776A
System and method for removing COD and calcium ions in cold rolling dilute alkali reverse osmosis concentrated water
CN112010385A
Multi-responsive core-shell lead ion imprinted polymer as well as preparation method and application thereof
CN118496445A
KR20230149084A
